SATISFACTION LEVEL OF RICE FARMERS TOWARD PARTNERSHIP PROGRAM WITH CORPORATE LOGISTICS (PERUM BULOG) IN SEMARANG CITY, INDONESIA - Adietya Muhammad Riezky; Siwi Gayatri; Joko Mariyono (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
The phenomenon of farmers selling their harvest has become a common thing. Solutions that can be offered are partnerships. Agricultural partnerships are expected to solve farmers' problems through facilitating product marketing. Partnerships between farmers and partner companies were sought out with cooperation agreements. This study aims to analyze important attributes related to the partnership program, and measure the level of farmer satisfaction with the partnership of Perum BULOG Semarang Branch Office. The study was carried out at the Ngudi Rejeki Gapoktan, Kendal Regency in November – December 2021. This study used a census, with a total of 110 farmers as respondents. The data collection method was interview. The type of data used were primary and secondary. Data analysis used were Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results show that the main priorities needed by farmers were guidance on the quality of harvests, assistance for harvest, guidance to improve farmers' capability, Perum BULOG provides a forum for continuous discussion, easy access to harvest delivery, and get shipping compensation. The result of CSI calculation was 65.1%, which indicated that farmers were satisfied with the performance of Perum BULOG Semarang Branch Office. However, there are a number of things that trigger farmers' dissatisfaction, including the increase in agricultural production prices, while the selling price of farmers' harvests is not always the same, the lack of communication between Gapoktan and Perum BULOG Semarang Branch Office, and the the price of HPP is still low.